A SIMA-Based Curriculum Data and Administration Management Model to Improve the Effectiveness of Teacher Performance in Public Senior High Schools in North Musi Rawas Regency - Meri Silvia; Nurul Astuty Yensy; Sudarwan Danim (Yayasan Sembilan Pemuda Indonesia, 2026)
Effective management of curriculum data and school administration is essential for improving teacher performance in public senior high schools. However, many schools still face challenges related to fragmented data systems, high administrative workloads, and limited integration between management information systems and teacher performance indicators. This study aims to develop and evaluate a SIMA-based curriculum data and administration management model to improve teacher performance effectiveness in public senior high schools in North Musi Rawas Regency. This research employed a research and development (R&D) approach, involving needs analysis, model design, development, implementation, and evaluation. Data were collected through questionnaires, observations, and documentation involving teachers and school administrators. Teacher performance effectiveness was measured before and after the implementation of the SIMA-based management model. Data analysis was conducted using descriptive and inferential statistical techniques to examine changes in teacher performance effectiveness. The results indicate that the developed SIMA-based curriculum data and administration management model is valid, practical, and effective. The implementation of the model significantly improved teacher performance effectiveness, particularly in administrative efficiency, time management, accuracy of academic data, and focus on instructional tasks. These findings suggest that integrating curriculum and administrative management through a SIMA-based system can reduce teachers’ administrative burden and enhance their professional performance. This study contributes theoretically to educational management research and practically provides a reference model for schools and policymakers seeking to improve teacher performance through integrated management information systems.